2019
DOI: 10.1002/smll.201805344
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hydrogen‐Substituted Graphyne Film for Lithium–Sulfur Battery Applications

Abstract: Graphyne (GY) is a new type of carbon allotrope, which is viewed as a rapidly rising star in the carbon family referred to as 2D carbon allotropes due to its extraordinary properties. Considering the dynamic nature of the alkyne metathesis reaction, a hydrogen‐substituted graphyne (HsGY) film is successfully synthesized on a gas/liquid interface using 1,3,5‐tripynylbenzene (TPB) as the precursor. The synthesized HsGY film is used as a sulfur host matrix to be applied in lithium–sulfur batteries (LSBs). The HsG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 53 publications
0
21
0
1
Order By: Relevance
“…However, the poor conductivity of sulfur (5 × 10 −30 S cm −1 at 25 °C) and high solubility of polysulfides result in the low reversible capacities and poor cycling performances of LSBs, thus hindering their widespread application . Various strategies have been explored to improve the performance of LSBs, including introducing porous materials into the cathodes, designing advanced composite cathodes, and modifying the separators . Porous carbons have been extensively used to enhance LSB performance because of their high SSA, well‐defined porosities, and excellent electrical conductivities .…”
Section: Applications Of Collagen‐derived Porous Carbons In Electrochmentioning
confidence: 99%
“…However, the poor conductivity of sulfur (5 × 10 −30 S cm −1 at 25 °C) and high solubility of polysulfides result in the low reversible capacities and poor cycling performances of LSBs, thus hindering their widespread application . Various strategies have been explored to improve the performance of LSBs, including introducing porous materials into the cathodes, designing advanced composite cathodes, and modifying the separators . Porous carbons have been extensively used to enhance LSB performance because of their high SSA, well‐defined porosities, and excellent electrical conductivities .…”
Section: Applications Of Collagen‐derived Porous Carbons In Electrochmentioning
confidence: 99%
“…As depicted in Figure 1c, a strong characteristic peak for the stretching vibration of the O-H or N-H groups [47] and a weak absorption band for the asymmetric stretching vibration of the -CH 2 group [48] were observed at 3415 and 2964 cm −1 , respectively. Besides this, the peaks that appeared at 1656 and 1577 cm −1 corresponded to the vibration of the C=O [49] and C=C [50] groups in the benzene ring, respectively. Moreover, the other peaks at 1400 and 1110 cm −1 indicated the existence of the -COOH and C-O [51] groups, separately.…”
Section: Characterization Of Fw-cdsmentioning
confidence: 93%
“… 26 It was reported that the reversible Na storage capacity reached as high as 580 mA h g −1 after 200 charge/discharge cycles, 25 and the theoretical simulations demonstrated the HsGY monolayer could provide numerous Na storage sites and delivered Na storage capacity of 1207 mA h g −1 . 25 Li et al 27 also synthesized HsGY film by alkyne metathesis reaction and demonstrated that HsGY can be used as lithium–sulfur battery. As anode material of LIBs, HsGY was revealed to have high capacity and excellent cycling stability.…”
Section: Introductionmentioning
confidence: 99%